Hybrid dynamic modeling-based membrane hydration analysis for the commercial high-power integrated PEMFC systems considering water transport equivalent. (1st February 2020) - Peng, Fei; Ren, Linjie; Zhao, Yuanzhe; Li, Liwei
Highlights: A hybrid model for PEMFC systems with water transport equivalent is developed. Parameters of the developed model are identified by a regional expansion method. The hypothesis of cathode micro-flooding operation of the PEMFC system is confirmed. The influence of cathode micro-flooding on PEMFC performance is analyzed. Differential current injection based self-healing control is discussed. Abstract: In this paper, the influence mechanism of proton exchange membrane hydration dynamics on the output characteristics of the commercial integrated 150 kW proton exchange membrane fuel cell (PEMFC) systems was investigated under actual operating conditions. On this basis, the control-oriented model was improved for the integrated PEMFC systems. On the one hand, the anode pressure following control and cathode backpressure regulation were equivalently modeled based on analysis of interactive control characteristics of the commercial high-power integrated PEMFC systems. On the other hand, equivalent modeling of membrane hydration dynamics inside the PEMFC stack was achieved, so as to reasonably characterize the effect of liquid water saturation on the output characteristics of the commercial integrated PEMFC systems, under the premise of not significantly affecting the model complexity. Moreover, the effectiveness of the improved control-oriented model was also verified through comparing the simulation and experimental results. Further analyses based on the developed system model showed that, online evaluation and self-healing control of the membrane hydration condition can be realized through dynamic analyses of the system voltage and current according to the differential current injection method such that reasonable membrane hydration condition can be ensured. Furthermore, up to 3.74% enhancement in the system efficiency was achieved in the case of minimized membrane micro-flooding, which was of great significance to improve the service life and operation reliability of the commercial integrated PEMFC systems.